2023
DOI: 10.1002/jia2.26054
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexualized drug use and risk of HIV among sexually active MSM in East and South Asian countries: systematic review and meta‐analysis

Abstract: Introduction Sexualized drug use (SDU), the use of psychoactive drugs in the context of sexual intercourse, has been identified as a risk factor for HIV among men who have sex with men (MSM) in Asia. Given the distinct social and cultural context of same‐sex relationships and drug‐using practice in Asia, we aimed to describe the prevalence of SDU in East and South Asian countries and its associations with condomless anal sex (CAI) and HIV status. Synthesizing SDU research in this region, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 106 publications
(210 reference statements)
0
5
0
2
Order By: Relevance
“…Our finding of an association between medium-to highrisk sexual practices and moderate-to high-risk substance use is consistent with numerous studies in which tobacco, alcohol, and illicit drugs were associated with unsafe sexual practices among those with or at risk of HIV. 10,12,17,18,20,[25][26][27] An association between depression and risky sexual behavior is well established, primarily in Western cohorts of MSM [28][29][30] ; however, evidence of association from the Asia-Pacific region is more limited. While a study of PLHIV in India found no association between depression and high-risk sexual behavior, 18 depression was associated with a history of STIs and seeking sexual partners through the Internet among MSM in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of an association between medium-to highrisk sexual practices and moderate-to high-risk substance use is consistent with numerous studies in which tobacco, alcohol, and illicit drugs were associated with unsafe sexual practices among those with or at risk of HIV. 10,12,17,18,20,[25][26][27] An association between depression and risky sexual behavior is well established, primarily in Western cohorts of MSM [28][29][30] ; however, evidence of association from the Asia-Pacific region is more limited. While a study of PLHIV in India found no association between depression and high-risk sexual behavior, 18 depression was associated with a history of STIs and seeking sexual partners through the Internet among MSM in China.…”
Section: Discussionmentioning
confidence: 99%
“…12 Sexualized drug use or the use of specific psychoactive substances during sexual activity to sustain, enhance, disinhibit, or facilitate the sexual experience 13 is prevalent among populations at risk of HIV in the region, particularly men who have sex with men (MSM) and transgender women, and is associated with unsafe sexual practices including condomless intercourse, multiple sex partners, and sexual exchange. [14][15][16][17] The prevalence of higher-risk sexual practices among adult PLHIV varies depending on sociodemographic and other factors such as age, sex, geographic location, concurrent substance use, and mental health disorders. 10,[18][19][20][21] Data from the Asia-Pacific region on the relationship between unsafe sexual practices, mental health disorders, and substance use are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the boundaries between hi-fun and other types of SDU were not well defined within service provider accounts. This tension is present across settings in Asia [ 26 , 27 ]; developing locally grounded understandings of the differences between hi-fun /chemsex relative to other SDU is an urgent priority necessary to support intervention design.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de la probable infraestimación derivada del registro, nos hemos encontrado con un alto porcentaje de personas que habían sufrido algún tipo de violencia a lo largo de sus vidas (37,2%), lo cual sería acorde con la asociación encontrada en algunas publicaciones (Strasser et al, 2023) entre antecedentes traumáticos, como los abusos sexuales o los delitos de odio, con la práctica de chemsex. No resulta sorprendente que una de cada 5 personas de la muestra sufrie-El alto porcentaje observado en nuestra muestra de personas con diagnóstico positivo de VIH (60%) resulta llamativo, aunque coherente con otras publicaciones que apuntan a una alta prevalencia de infección por VIH en usuarios de chemsex (González-Baeza et al, 2023;MacGregor et al, 2021;Nevendorff et al, 2023;Vallecillo et al, 2022;Whitlock et al, 2021). Dado el tipo de estudio y la forma de recogida de la información, desconocemos si el diagnóstico de VIH es previo o posterior al inicio de la práctica.…”
Section: Discussionunclassified